Les démarches de chercheurs en physique et en mathématiques. Enjeux didactiques d'une nouvelle approche épistémologique - Suzane El Hage; Cécile Ouvrier-Buffet (Nantes Université, 2018)
Inquiry-based Education (IBE) is presented as derived from scientific approaches. In this paper, we examine the epistemology used by didacticians in Science and Mathematics; we show the need to adopt a new epistemological posture in didactics to enrich the teaching of scientific approaches in Science and Mathematics. In particular, we have questions about the research processes used by the contemporary researchers, in Physics and Mathematics; we model them in a comparative perspective. The theoretical framework chosen (a model of conceptions) is demonstrated that efficient and transdisciplinary. The results show, especially, convergences and divergences between the researchers in both Physics and Mathematics fields; the findings bring also new questions for the research in didactics of Sciences and Mathematics regarding the transposition and the implementation of scientific approaches in classrooms.